Regular insulin added to total parenteral nutrition vs subcutaneous glargine in non-critically ill diabetic inpatients, a multicenter randomized clinical trial: INSUPAR trial. Issue 2 (February 2020) - Olveira, Gabriel; Abuín, Jose; López, Rafael; Herranz, Sandra; García-Almeida, Jose M.; García-Malpartida, Katherine; Ferrer, Mercedes; Cancer, Emilia; Luengo-Pérez, Luis M.; Álvarez, Julia; Aragón, Carmen; Ocón, María J.; et al.
Summary: Background: There is no established insulin regimen in T2DM patients receiving parenteral nutrition. Aims: To compare the effectiveness (metabolic control) and safety of two insulin regimens in patients with diabetes receiving TPN. Design: Prospective, open-label, multicenter, clinical trial on adult inpatients with type 2 diabetes on a non-critical setting with indication for TPN. Patients were randomized on one of these two regimens: 100% of RI on TPN or 50% of Regular insulin added to TPN bag and 50% subcutaneous GI. Data were analyzed according to intention-to-treat principle. Results: 81 patients were on RI and 80 on GI. No differences were observed in neither average total daily dose of insulin, programmed or correction, nor in capillary mean blood glucose during TPN infusion (165.3 ± 35.4 in RI vs 172.5 ± 43.6 mg/dL in GI; p = 0.25). Mean capillary glucose was significantly lower in the GI group within two days after TPN interruption (160.3 ± 45.1 in RI vs 141.7 ± 43.8 mg/dL in GI; p = 0.024). The percentage of capillary glucose above 180 mg/dL was similar in both groups. The rate of capillary glucose ≤70 mg/dL, the number of hypoglycemic episodes per 100 days of TPN, and the percentage of patients with non-severe hypoglycemia were significantly higher on GI group. No severe hypoglycemia was detected. No differences were observed in length of stay, infectious complications, or hospital mortality. Conclusion: Effectiveness of both regimens was similar. GI group achieved better metabolic control after TPN interruption but non-severe hypoglycemia rate was higher in the GI group. Clinical trial registry: This trial is registered at clinicaltrials.gov as NCT02706119 .